Mosaic KRAS Mutation in Schimmelpenning–Feuerstein–Mims Syndrome With Overlapping Oculoectodermal Syndrome and Encephalocraniocutaneous Lipomatosis Features - Hyvönen, Hanna; Kettunen, Kaisa; Avela, Kristiina; Kivirikko, Sirpa; Jeskanen, Leila; Suominen, Sinikka; Salminen, Päivi; Hannula‐Jouppi, Katariina (Wiley, 2025)
We report a patient with clinically confirmed Schimmelpenning-Feuerstein-Mims (SFM) syndrome but many overlapping features with oculoectodermal syndrome (OES) and encephalocraniocutaneous lipomatosis (ECCL). Whole exome sequencing revealed a mosaic KRAS c.436G>A, p.(Ala146Thr) mutation, previously identified in three OES and ECCL patients. These findings corroborate the evidence of SFM syndrome being a mosaic RASopathy, broaden the phenotypic spectrum of oculocutaneous mosaic RASopathies, and indicate SFM syndrome as a continuum of the OES-ECCL disorder spectrum.